Ocean-Atmosphere Interactions of Gases and Particles - Liss, Peter S.; Johnson, Martin T. (Springer Earth System Sciences, 2014)
Earth System Sciences; Environmental Chemistry; Climatology; Marine & Freshwater Sciences; Atmosphere ocean interaction; Chemical Exchanges; Biogeochemistry; COST 735; air-sea interface; Trace gases; SOLAS